Past and current routes to β-hydroperoxy alcohols: A functional group with high potential in organic synthesis. (24th September 2021) - Bordier, Corentin; Escande, Vincent; Darcel, Christophe
Abstract: This review aims to showcase the high potential of β-hydroperoxy alcohols (HPA) as intermediates in molecular chemistry in both academic and industrial areas. In particular, these are crucial intermediates for the synthesis of 1, 2, 4-trioxanes, essential motifs in numerous anti-malarial drugs including the lead artemisinin. The aim of this review is to report the main pathways of preparation of HPAs, more particularly highlighting the selective opening of epoxides by hydrogen peroxide solutions or the use of singlet oxygen for the photooxygenation of allylic alcohols. © 2021 Elsevier Science. All rights reserved. Graphical abstract: Image 1